If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -13 + -2b = b + -7 Reorder the terms: -13 + -2b = -7 + b Solving -13 + -2b = -7 + b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-1b' to each side of the equation. -13 + -2b + -1b = -7 + b + -1b Combine like terms: -2b + -1b = -3b -13 + -3b = -7 + b + -1b Combine like terms: b + -1b = 0 -13 + -3b = -7 + 0 -13 + -3b = -7 Add '13' to each side of the equation. -13 + 13 + -3b = -7 + 13 Combine like terms: -13 + 13 = 0 0 + -3b = -7 + 13 -3b = -7 + 13 Combine like terms: -7 + 13 = 6 -3b = 6 Divide each side by '-3'. b = -2 Simplifying b = -2
| -3p+8=5-(8p+4) | | 2-8(4y-7)= | | (2.35+2.71i)-(4.91+3.32i)=0 | | 1x+7=3x+1 | | n/5=1.6 | | 6(t-2)+8t=7(2t+4)-9 | | 7x+3y+x=16+3 | | 4+(6-7p)-2= | | 7x+1=5x-3 | | 3(x+9)=18 | | -14b+7a+2a=-5b | | x+(x+28)(2x-38)=652 | | 2y^3-13y^2+6y=0 | | x^3+x^2+2x+2=0 | | 16v^6w^7+22v^2w^6y^4= | | 7x-10=15+2x | | x-42=51 | | 3mx^2-2mx+2=x(6-5x) | | 5x-4y+9y=-15x+5 | | x+8=29 | | 0.6x+7=21 | | 8m-15m=56 | | 80z^8-45z^6=0 | | 3d-5=7d-12 | | 0.5x-4=6 | | -2t+4t-7s=9s | | 0.4x+10=20 | | 8+3(s-4t)= | | -4y-3x-x=-16y | | 3y-2x^2=x | | (m-2)x^2-mx-m= | | 2(x-3)=3(x+1)-5 |